STUDENT’S PERCEPTIONS OF PRECEPTORSHIP LEARNING OUTCOMES IN BSN PROGRAM AT PRIVATE AND PUBLIC SCHOOLS OF NURSING IN SINDH - Victoria Samar1, Shireen Arif2, Alia Nasir3, Amanullah Rind Baloch4, Sara Samar5, Asnath Samar6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: The aim of the study is to assess student’s perceptions about learning outcomes of the preceptorship model utilized during their BSN program and to identifytheir level of satisfaction. METHODOLOGY: In this cross-sectional study 182 students participated from one public and one private college of nursing. Structured questionnaire named Preceptorship Effectiveness Questionnaire: Student Perceptions (PEQ-SP) developed by Shepard in 2014 was utilized. The permission to adapt the questionnaire for this study was granted by primary author. RESULTS: The results of the study clearly stated that all three themes, that are SPR-EPP, HoP and OSsignificantly correlated to each-other with p-values<0.01 in all three themes. Moreover, the satisfaction rate of students regarding their preceptors washighly significant with p-value <0.01. CONCLUSION: The study findings suggest that the preceptorship program should be implemented in other clinical courses. This will be beneficial for both clinical and academic institutions for better student’s learning as well as better patient outcomes.